PENERAPAN MEDIA FLASHCARD UNTUK MENINGKATKAN KECERDASAN LINGUISTIK ANAK USIA DINI DALAM PENGENALAN HURUF DI RA AL HIDAYAH PESAWAHAN - Taofah, Mufti; Mulyani, Novi (EDUCHILD (Journal of Early Childhood Education), 2024)
Linguistic Intelligence is one of the crucial aspects of development in early childhood. Language skills influence children's ability to communicate, read, write and listen, which is the basis of the subsequent learning process. Recognition of letters is the first step in a child's language or linguistic development. Using flashcards as a learning tool can provide interesting visual stimulation and make it easier for children to remember and recognize letters. This research aims to describe how teachers implement it in improving linguistic intelligence with flashcard tools or media at RA Al Hidayah Pesawahan. The method used in this research is qualitative methods with case study research. The research subjects were teachers and students. Flashcard media is a learning medium to introduce simple letters and words which can make it easier for children to learn. Flashcards containing pictures of alphabet letters, vegetables, transportation, and so on. The results of the research show that the application of flashcard media to improve children's linguistic intelligence in recognizing letters in children goes through several stages carried out by the teacher, including planning through habituation activities which are carried out every morning before entering class, one child takes a card at random and pronounces the letter. on the card to the teacher. The evaluation carried out is that the teacher looks at the process of each child's ability to pronounce it. Of the 25 children, 17 of them were able to pronounce letters and spelling without help from other people.